Effects of feeder design and pelleting on growth performance and water use in finishing pigs - M M Rantanen; Robert H Hines; I H Kim; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1995)
Pigs fed from wet-dry feeders had 4% greater ADG with 50% less water usage than those consuming feed from dry feeders. Pelleting diets improved F/G by 4% compared to meal diets. However, the benefits of pelleting were primarily when a dry feeder was used, with little evidence to support use of both pelleting and wet/dry feeders for finishing pigs.; Swine Day, Manhattan, KS, November 16, 1995
Keywords: Swine day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-140-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 746; Swine; Finishing pigs; Feeders; Pellet